Translation Reception of Brazilian Literature in Serbia (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2025)
This study examines the trajectory of Brazilian literature in Serbia, a cultural sphere where geographic distance and limited prior exposure long constrained its visibility. Although its presence is still comparatively modest – both in relation to other foreign literatures in Serbia and to its circulation in various international contexts – several dozen Brazilian works have nonetheless been published in translation from the early twentieth century to the present. The research maps this evolution by compiling data from previous scholarship, the National Library of Serbia’s catalogue, and archival materials held at the Embassy of Brazil in Belgrade. The analysis identifies three distinct phases in the publication of Brazilian literary translations. The first corresponds to the Yugoslav period, when a shared linguistic and publishing space facilitated translations across republics, including those originating in Croatia. The second phase begins after the dissolution of Yugoslavia, marked by a drastically reduced editorial market limited to Serbia and Montenegro. The third phase is defined by the transformative impact of the 56th Belgrade International Book Fair (2011), at which the entire Portuguese-speaking world was featured as Guest of Honour – a milestone that broadened readers’ expectations horizon and reshaped the reception of Lusophone literatures in Serbia.
Keywords: Brazilian literature; translation reception; Portuguese language; literary translation